2022
DOI: 10.1186/s12967-022-03753-5
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral acute lung injury in pig: a promising animal model

Abstract: Background Acute lung injury (ALI) occurs in 23% unilateral. Models of unilateral ALI were developed and used previously without clearly demonstrating the strictly unilateral nature and severity of lung injury by the key parameters characterizing ALI as defined by the American Thoracic Society (ATS). Thus, the use of unilateral ALI remained rare despite the innovative approach. Therefore, we developed a unilateral model of ALI and focused on the crucial parameters characterizing ALI. This model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…173 Some studies have shown a pioneering model of unilateral ALI, induced by cyclic rinsing with 0.9% saline and 0.3% Triton X-100 in mechanically ventilated pigs. 174 Genome-wide association analysis has allowed researchers to recognize the contribution of genetic background to IPF, leading to the development of some genetically engineered mice to mimic the process of spontaneous pulmonary fibrosis. AT2 cell targeted knockout telomeric repeat binding factor 1 mice exhibit spontaneous pulmonary fibrosis characteristics through telomere damage.…”
Section: Bleomycin-induced Lung Injury Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…173 Some studies have shown a pioneering model of unilateral ALI, induced by cyclic rinsing with 0.9% saline and 0.3% Triton X-100 in mechanically ventilated pigs. 174 Genome-wide association analysis has allowed researchers to recognize the contribution of genetic background to IPF, leading to the development of some genetically engineered mice to mimic the process of spontaneous pulmonary fibrosis. AT2 cell targeted knockout telomeric repeat binding factor 1 mice exhibit spontaneous pulmonary fibrosis characteristics through telomere damage.…”
Section: Bleomycin-induced Lung Injury Modelmentioning
confidence: 99%
“…For vascular ECs, there are different injury modes such as intravenous injection of oleic acid, LPS, and endotoxin 173 . Some studies have shown a pioneering model of unilateral ALI, induced by cyclic rinsing with 0.9% saline and 0.3% Triton X‐100 in mechanically ventilated pigs 174 …”
Section: Research Models Of Lung Injury and Regenerationmentioning
confidence: 99%
“…Pigs, due to their anatomical size and structure, physiology, immunology, and genome similarity to humans, have been utilized in the investigation of various lung diseases [131,132]. A model of unilateral acute lung injury in pigs has been established, validated by histopathology and an inflammatory response [133]. This model can serve as a basis for comparing the pathophysiological changes in both the injured and uninjured lungs within the same animal [133], and holds potential for the study of AE-IPF in the future.…”
Section: Other Models Of Ae-pfmentioning
confidence: 99%
“…A model of unilateral acute lung injury in pigs has been established, validated by histopathology and an inflammatory response [133]. This model can serve as a basis for comparing the pathophysiological changes in both the injured and uninjured lungs within the same animal [133], and holds potential for the study of AE-IPF in the future. Numerous studies have explored the utilization of sheep as an animal model for pulmonary fibrosis.…”
Section: Other Models Of Ae-pfmentioning
confidence: 99%
“…In order to better understand the development mechanism of lung pathology, numerous animal models of lung injury have been established [ 2 , 3 ]. The disease models of bleomycin (BLM)-induced pulmonary fibrosis (BIPF) and radiation-induced lung injury (RILI) are commonly used in oncology since they can better mimic the successive progression of pneumonitis and lung fibrosis after drug treatment or radiotherapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%